2019
DOI: 10.1039/c9py00926d
|View full text |Cite
|
Sign up to set email alerts
|

An amphiphilic, heterografted polythiophene copolymer containing biocompatible/biodegradable side chains for use as an (electro)active surface in biomedical applications

Abstract: Design of an amphiphilic heterografted block copolymer composed of a hydrophobic core backbone and both hydrophilic side chains, able to detect the redox reaction of NADH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…61 This strategy has been successfully used for the preparation of conductive films for other biomedical applications. 62,63…”
Section: Electro-stimulated Peptide Releasementioning
confidence: 99%
“…61 This strategy has been successfully used for the preparation of conductive films for other biomedical applications. 62,63…”
Section: Electro-stimulated Peptide Releasementioning
confidence: 99%
“…These materials take advantage of the unique electrochemical and electrical properties of CPs and the chemical and/or physical properties of the grafted side chains. For example, conducting grafted copolymers have been used to fabricate electrochemical sensors for bioanalytics (e,g quantitative detection of NADH, serotonin, dopamine, cocaine and non-Hodgkin lymphoma gene); [15][16][17][18][19] to construct surfaces with antimicrobial 16 or imaging activity; 20 to prevent the non-specific adhesion of cells and proteins; 21,22 to prepare nanocarrier systems that enable size-selective encapsulation of drug molecules and their sustained release; 23 and to promote cell activity for tissue engineering. [24][25][26] Graft copolymers with CP backbones and flexible, stimuli-sensitive side chains are interesting polymeric architectures that, in former reports, were also named "molecular composites" based on their macroscopic properties.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 This type of polymers can be prepared using three different approaches: 29 1) "grafting to" in which endfunctionalized side chains (already polymerized) are connected to reactive sites of the CP backbone; 2) "grafting from" that consists on the growing of the side chains from the initiation sites of the CP; and 3) "grafting through", which involves the synthesis of electroactive macromonomers that can be homopolymerized 22 or copolymerized with an appropriate low-molecular weight compound 16,17,20 or with another macromonomer. 15 The "grafting through" strategy allows for the tuning of side chains grafting density and branching points distance adjustment, giving the possibility to modulate the materials properties for a targeted application. 30,31 In recent years we have used such an approach to prepare graft copolymers having polythiophene backbone and polyethylene glycol (PTh-g-PEG) as side chains.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases [ 41 , 42 ], the introduction of PCL side chains to the conjugated backbones has contributed to increased biocompatibility and efficiency when working in biorelevant aqueous electrolytes of the obtained materials. In the case of a heterografted polythiophene, such introduction contributed to the development of a material whose weight was composed mainly of PCL and PEG commodity polymers [ 43 ], which also showed that its amphiphilic nature allows for the manipulation of the self-assembled morphology by solvent selectivity and concentration of solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this study, we focused on showing the impact of the final EDOT group on OCL properties and investigating the EDOT-PCL capacity of self-assembly in solution and the subsequent morphological transitions that occurred during thin film formation. The solvents used, chloroform (Chl) and acetonitrile (ACN), were deliberately chosen in order to show the significant influence caused by their difference in polarity and because they are commonly used as reaction media for chemical and electrochemical polymerization [ 42 , 43 , 51 ]. An explanation is also given for the transition from colorless to blue color that was observed during the preparation of a concentrated solution of EDOT-PCL in CDCl3.…”
Section: Introductionmentioning
confidence: 99%